Implementasi Algoritma C4.5 Untuk Memprediksi Capaian Pembelajaran Daring (Studi Kasus Siswa MAN 3 Blitar) - Hidayatuloh, Muchamad Azis; Kartika, Kurnia Paranita; Permadi, Dimas Fanny Hebrasianto (Algoritme Jurnal Mahasiswa Teknik Informatika, 2022)
Learning outcomes are focused on what students want to be able to do during or at the end of a learning process that includes the learning and teaching process. The problem when learning online is that there are network constraints and the lack of teaching hours for teachers and the limited amount of material that can be delivered. So a solution is needed to determine the level of student satisfaction in the process of achieving online learning in schools. This study applies the C4.5 algorithm for the classification of online learning outcomes at MAN 3 Blitar. This study aims to predict the achievement of online learning with the C4.5 algorithm. There are 10 attributes that affect the achievement of online learning, namely: remembering, attendance, assignments, assessment, material, conditions, application, creating, discussion, analysis. With research, it can make it easier for teachers to determine online learning methods with minimal constraints. The results of the research using the C4.5 algorithm are 27 decision trees and rules, the highest gain value is the Create attribute, which is 0.383923. The results of the validation test using the confusion matrix level of accuracy in predicting online learning achievement on average are 88%, precision is 83%, recall is 86%. With the results of the accuracy value obtained, it can be said to be included in the Good Classification.